Oblique Lateral Interbody Fusion versus Transforaminal Lumbar Interbody Fusion in Degenerative Lumbar Spondylolisthesis: A Single-Center Retrospective Comparative Study. (22nd March 2021) - Du, Xing; She, Yuxiao; Ou, Yunsheng; Zhu, Yong; Luo, Wei; Jiang, Dianming
Abstract : Objective . To compare the efficacy of oblique lateral interbody fusion (OLIF) and transforaminal lumbar interbody fusion (TLIF) in single-level degenerative lumbar spondylolisthesis (DLS). Methods . A retrospective analysis of patients who underwent single-level DLS surgery in our department from 2015 to 2018 was performed. According to the surgical method, the enrolled patients were divided into two groups, namely, the OLIF group who underwent OLIF combined with percutaneous pedicle screw fixation (PPSF) and the TLIF group. Clinical outcomes included operation time, operation blood loss, postoperative drainage, hospital stay, visual analog scale (VAS) score, Oswestry disability index (ODI), and complications, and imaging outcomes included upper vertebral slip, intervertebral space height (ISH), intervertebral foramen height (IFH), intervertebral space angle (ISA), lumbar lordosis (LL), and bone fusion rate. All outcomes were recorded and analyzed. Results . A total of 65 patients were finally included, and there were 28 patients and 37 patients in the OLIF group and the TLIF group, respectively. The OLIF group showed shorter operation time, less blood loss, less postoperative drainage, and shorter hospital stay than the TLIF group (P < 0.05 ). The ISH, IFH, ISA, and LL were all larger in the OLIF group at postoperative and last follow-up (P < 0.05 ), but the degree of upper vertebral slip was found no difference between the two groups (P > 0.05 ). The bone graft fusion rate of OLIF group and TLIF group at 3 months, 6 months, and last follow-up was 78.57%, 92.86%, and 100% and 70.27%, 86.49%, and 97.30%, respectively, and no significant differences were found (P > 0.05 ). Compared with the TLIF group, the OLIF group showed a superior improvement in VAS and ODI at 1 month, 3 months, and 6 months postoperative (P < 0.05 ), but no differences were found at 12 months postoperative and the last follow-up (P > 0.05 ). There was no significant difference in complications between the two groups, with 4 patients and 6 patients in the OLIF group and TLIF group, respectively (P > 0.05 ). Conclusions . Compared with TLIF, OLIF showed the advantages of less surgical invasion, better decompression effect, and faster postoperative recovery in single-level DLS surgery.